Exosomes combined with biomaterials in the treatment of spinal cord injury - Zhang, Xuanxuan; Jiang, Wenwei; Lu, Yan; Mao, Tiantian; Gu, Yu; Ju, Dingyue; Dong, Chuanming (Frontiers in Bioengineering and Biotechnology, 2023)
Spinal cord injury (SCI) is a serious and disabling disease with a high mortality rate. It often leads to complete or partial sensory and motor dysfunction below the plane of injury and is accompanied by a series of secondary diseases, such as pressure sores, pulmonary infections, deep vein thrombosis in the lower extremities, urinary tract infections, and autonomic dysfunction. Currently, the main treatments for SCI include surgical decompression, drug therapy, and postoperative rehabilitation. Tissue engineering studies have shown that cell therapy plays a beneficial role in the treatment of SCI, however, there is a controversy about the therapeutic effect of stem cells in SCI models. Meanwhile exosomes, as a new therapeutic medium for regenerative medicine, possess the advantages of small size, low immunogenicity, and the ability to cross the blood-spinal cord barrier. Certain studies have shown that stem cell-derived exosomes have anti-inflammatory effects and can play an irreplaceable role in the treatment of SCI. In this case, it is difficult for a single treatment method to play an effective role in the repair of neural tissue after SCI. Meanwhile, the combination of biomaterial scaffolds and exosomes can better transfer and fix exosomes to the injury site and improve the survival rate. This paper reviews the current research status of stem cell-derived exosomes and biomaterial scaffolds in the treatment of SCI, respectively, and describes the application of exosomes combined with biomaterial scaffolds in the treatment of SCI, as well as the challenges and prospects.